Nansenhjelpens historie og aktiviteter : en norsk humanitær organisasjon i tsjekkisk perspektiv - Eva Dohnálková (Brünner Beiträge zur Germanistik und Nordistik, 2014)
This article deals with the Norwegian humanitarian organisation Nansenhjelpen and is based on master theses defended in January 2014 at Faculty of Arts at Masaryk University in Brno. The article focuses mainly on the activities of the organisation in Czechoslovakia as this topic has been rarely discussed so far. Partner organisation on Czech side are shortly presented, but the article describes mainly a rescue campaign of Nansenhjelpen in which a group of about 37 children was transported from Czechoslovakia to Norway. Children were placed in foster families or the jewish children's home in Oslo. Some of the children were however sent back to Czechoslovakia on their parents' demand and 14 of remaining children later fled to Sweden.